2015
DOI: 10.3109/09537104.2015.1042967
|View full text |Cite
|
Sign up to set email alerts
|

Altered plasma fibrin clot properties in essential thrombocythemia

Abstract: Patients with increased thromboembolic risk tend to form denser fibrin clots which are relatively resistant to lysis. We sought to investigate whether essential thrombocythemia (ET) is associated with altered fibrin clot properties in plasma. Ex vivo plasma fibrin clot permeability coefficient (Ks), turbidimetry and clot lysis time (CLT) were measured in 43 consecutive patients with ET (platelet count from 245 to 991 × 10(3)/µL) and 50 control subjects matched for age, sex and comorbidities. Fibrinolysis prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
(49 reference statements)
3
11
0
2
Order By: Relevance
“…Soluble P‐selectin promotes NET formation . Moreover, the associations between sP‐selectin and both K s and CLT support growing evidence for the impact of platelet‐derived proteins on clot properties reported previously …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Soluble P‐selectin promotes NET formation . Moreover, the associations between sP‐selectin and both K s and CLT support growing evidence for the impact of platelet‐derived proteins on clot properties reported previously …”
Section: Discussionsupporting
confidence: 85%
“…40 Moreover, the associations between sP-selectin and both K s and CLT support growing evidence for the impact of platelet-derived proteins on clot properties reported previously. 41 We confirmed that older age 42 and higher platelet count 7 can predict cancer diagnosis following unprovoked VTE. We did not find male sex to be a risk factor, as opposed to the studies by Jara-Palomares et al 7 and Rieu et al, 43 although evidence for this issue is inconsistent.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies indicate that K s measurement might be a suitable tool for clinical use; however, differences in the results, given the use of various concentrations of reagents and techniques in laboratories, limit its current applicability and require further efforts to standardize this technique, which has huge potential clinical implications. Prospective studies are Atherosclerotic vascular diseases Stable coronary artery disease, 48 peripheral arterial disease 49 Thromboembolic arterial events Acute coronary syndromes, 28 no-reflow phenomenon after acute MI, 50 instent thrombosis, 51 previous ischemic stroke, 29 acute ischemic stroke 52 Other cardiovascular diseases Chronic heart failure with sinus rhythm, 53 atrial fibrillation (paroxysmal, persistent, and permanent), 37,54 arterial hypertension 55 Venous thrombosis Idiopathic venous thromboembolism, 56 cerebral venous sinus thrombosis 57 Chronic renal disease End-stage renal disease on peritoneal dialysis 58 and long-term hemodialysis 59 Malignancy Digestive tract cancer, 60 multiple myeloma, 61 essential thrombocythemia 62 Autoimmune or chronic inflammatory diseases Inflammatory bowel disease, 63 antiphospholipid syndrome, 64,65 rheumatoid arthritis 66 Other Factor XIII Val34Leu polymorphism, 67 elevated plasma lipoprotein(a), 68 familial history of premature coronary artery disease 27 or venous thromboembolism 69 Increased K s…”
Section: Resultsmentioning
confidence: 99%
“…The structure of fibrin networks is often affected by physical factors, such as hydrodynamic flow or a strong magnetic field that result in formation of oriented anisotropic fibrin fibers (Gersh et al 2010; Campbell et al 2010). Fibrin structure and properties are greatly influenced by the presence of blood cells, namely activated platelets and erythrocytes (Aleman et al 2014; Malecki et al 2015) that form a natural and very active environment for clot formation. In addition to whole cells, the effects of circulating cell-derived microparticles on the fibrin clot structure and properties have been recently demonstrated (Zubairova et al 2015).…”
Section: 4 Variations and Modulation Of Fibrin(ogen) Structure Andmentioning
confidence: 99%